2021
DOI: 10.1002/bmc.5253
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetic study of six lignans in normal and diabetic rats after oral administration ofSaururus chinensisextract by LC–MS/MS

Abstract: Saururus chinensis (SC) possesses significant anti-diabetic activity and lignans were its major bioactive compounds. In this study, a rapid and sensitive ultra-highperformance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method was established for simultaneous quantification of six lignans, namely (-)-(7R,8R)-machilin D (1), verrucesin (2), rel-(7S,8S,7 0 R,8 0 R)-3,3 0 ,4,4 0 ,5,5 0hexamethoxy-7.O.7 0 ,8.8 0 -lignan (3), manassantin A (4), manassantin B (5), and saucerneol F (6) in rat's plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Notably, most of the current PK studies are in normal animals, and there are fewer in model animals. Numerous studies have shown that disease states may cause significant alterations in PK parameters ( Chen et al, 2022 ; Liu et al, 2022 ; Xiong et al, 2023 ). Since the drugs are mainly used in the pathological state of the body, it is more meaningful to study the PK of TCM in pathological states ( Luo et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, most of the current PK studies are in normal animals, and there are fewer in model animals. Numerous studies have shown that disease states may cause significant alterations in PK parameters ( Chen et al, 2022 ; Liu et al, 2022 ; Xiong et al, 2023 ). Since the drugs are mainly used in the pathological state of the body, it is more meaningful to study the PK of TCM in pathological states ( Luo et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…10,11 However, most of the literature is limited to the structural elucidation and/or bioactivity of isolated compounds or even a single compound. Only a few studies have relied on chromatographic profiling, such as liquid chromatography-mass spectrometry 12,13 or gas chromatography-mass spectrometry 14 or HPLC coupled with multiple-stage tandem mass spectrometry using electrospray ionization (HPLC-ESI-MS n ), 15,16 to obtain more comprehensive results, but numerous minor constituents remained undetected. Thus, the data on the detailed chemical profiles and relative abundances of lignans in Dendrobium are still lacking.…”
Section: Introductionmentioning
confidence: 99%